Experimental characterization of the mechanical properties of PETG and PA6 thermoplastics (2018)
Simple thermoplastic materials and polymer matrix composites have been used in this work. Polyethylene terephthalate glycol (PETG) plates, a copolymer of CHDM- cyclohexane dimethanol modified polyethylene terephthalate [56], were used, which is an amorphous and therefore transparent material, which was available in plates or extruded sheets in a wide range of thicknesses. The PETG sheets are of commercial type and their production process is carried out by the company that supplied them. Also part of the study is polyamide 6.6 with 30% short glass fibre content obtained by injection moulding and compression moulding, which was supplied by the ESIS TC4, for the first Round Robin of short glass fibre composite materials.